Prehistoric life : [the definitive visual history of life on earth] - Palmer, Douglas; Lamb, Simon; Gavira Guerrero, Angeles; Frances, Peter; DK Publishing, Inc. (New York, N.Y. : DK Pub., 2012)
With an extensive catalog at its heart, "Prehistoric Life" profiles hundreds of fascinating species in incredible detail; features breathtaking, state-of-the-art images; explores the concept of geological time; and explains the classification of species and how the evidence for their evolution is preserved and can be deciphered.
Young earth. Exploring earth's past -- The origin of the earth -- The first 500 million years -- Plate tectonics -- Changing climates -- Life and evolution -- Classification -- Mass extinctions -- Types of fossils -- Information in the fossil record -- Key fossil sites -- The geological timescale -- Life on earth. Archean -- Proterozoic -- Cambrian -- Ordovician -- Silurian -- Devonian -- Carboniferous -- Permian -- Triassic -- Jurassic -- Cretaceous -- Paleogene -- Neogene -- Quaternary -- The rise of the humans. Human relatives -- Human ancestors -- Origins of modern humans -- Out of Africa -- European hunter gatherers -- Paleolithic cave art -- After the ice.
At head of title: DK.
Subtitle from cover.
Includes index.
Keywords: Fossils; Fossils -- Pictorial works; Animals, Fossil; Animals, Fossil -- Pictorial works; Plants, Fossil; Plants, Fossil -- Pictorial works; Fossil hominids; Fossil hominids -- Pictorial works; Paleobiology; Earth (Planet) -- Origin; Earth (Planet) -- Origin -- Pictorial works